MalDA, Accelerating Malaria Drug Discovery. Issue 6 (June 2021) - Yang, Tuo; Ottilie, Sabine; Istvan, Eva S.; Godinez-Macias, Karla P.; Lukens, Amanda K.; Baragaña, Beatriz; Campo, Brice; Walpole, Chris; Niles, Jacquin C.; Chibale, Kelly; Dechering, Koen J.; Llinás, Manuel; et al.
Abstract : The Malaria Drug Accelerator (MalDA) is a consortium of 15 leading scientific laboratories. The aim of MalDA is to improve and accelerate the early antimalarial drug discovery process by identifying new, essential, druggable targets. In addition, it seeks to produce early lead inhibitors that may be advanced into drug candidates suitable for preclinical development and subsequent clinical testing in humans. By sharing resources, including expertise, knowledge, materials, and reagents, the consortium strives to eliminate the structural barriers often encountered in the drug discovery process. Here we discuss the mission of the consortium and its scientific achievements, including the identification of new chemically and biologically validated targets, as well as future scientific directions. Highlights: Novel antimalarial therapies are required to combat drug-resistant Plasmodium falciparum (Pf) and help with malaria elimination. To address the need for antimalarial drugs, Malaria Drug Accelerator (MalDA), a public–private partnership, was formed in 2012. Today, it is a consortium of 15 academic and industrial laboratories whose collective expertise and resources have been brought together to accelerate malaria drug development. Over the last decade, MalDA has developed a collaborative pipeline, applying multiple biomedical, biotechnological, and cheminformatic approaches to the identification of novel drug targets. Due to the significant progress in identifying novel validated targets, advanced target-based drug discovery is underway. Chemists are performing hit-to-lead compound optimization on inhibitors of many chemically validated targets, including Pf phenylalanyl-tRNA synthetase ( PheRS), Pf acetyl-CoA synthetase (AcAS), and Pf Niemann–Pick type C1-related protein (NCR1).